Returning to Climb after Epiphyseal Finger Stress Fracture - Meyers, Rachel N.; Schöffl, Volker Rainer; Mei-Dan, Omer; Provance, Aaron J. (Current Sports Medicine Reports, 2020)
The number of youth participating in rock climbing has increased over the years. Finger stress epiphyseal fractures are the most common injury among youth climbers. These injuries tend to occur around puberty because this is when the physis is most vulnerable to injury. Additionally, it has been found that intensive finger training (campus boarding, a previously known risk factor for epiphyseal fractures) during adolescence can lead to early-onset osteoarthritis of the hand up to a decade later. There is currently a lack of a return-to-climb protocol for youth climbers following a repetitive stress epiphyseal fracture. Because of this gap in the literature, our purpose was to create a structured return-to-play protocol specific to youth climbers who sustained an epiphyseal fracture to the finger. By establishing these guidelines, medical professionals and coaches may be able to guide their athlete to gradually and safely return to sport.
CRIS-Team Scopus Importer:2020-11-20